Porosity and permeability prediction using pore geometry structure method on tight carbonate reservoir. (June 2020) - Mulyanto, B S; Dewanto, O; Yuliani, A; Yogi, A; Wibowo, R C
Abstract: Porosity and Permeability is an essential petrophysical parameter of hydrocarbon reservoirs for oil and gas production. It's can be immediately measured using cores taken from the reservoir in the laboratory and deal with the high cost. Many empirical, statistical, and intelligent approaches were suggested to predict permeability in un-cored wells based on wireline logs. The main objective of this study is to predict the porosity and permeability values in a tight carbonate reservoir. In this study, the calculation of permeability was done using the Schlumberger, East, Morris Biggs Oil, Morris Biggs Gas, and PGS (Pore Geometry Structure) methods based on core, logs, and CT-Scans data. The determination of porosity values from CT-Scan performed on 20 core plugs from two data cores, each core plugs was plotted as many as 15 points. The output is the CT-Porosity value that will be used for the distribution of predictions of PGS permeability. Based on the result, porosity and permeability range value from 5 – 11%; 0.015 – 24.5 mD and presents a poor to fair reservoir quality.